2019
DOI: 10.15171/jcs.2019.029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Self-Management Program on Self-efficacy and Medication Adherence in Patients with Mechanical Heart Valve: a Randomized Clinical Trial

Abstract: Introduction:Patients with mechanical heart valve need anticoagulant therapy to prevent thrombotic events. The treatment interacts with some foods and drugs. The aim was to evaluate the effect of self-management program on self-efficacy and medication adherence in patients with mechanical heart valve. Methods: This was a randomized controlled trial. eighty eligible patients, with the ability to read and speak in Farsi, aged between 15 to 60, were included in the study from the cardiac surgery clinic in Imam Kh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(22 citation statements)
references
References 24 publications
(27 reference statements)
0
22
0
Order By: Relevance
“…Among the included studies, 8 studies demonstrated positive effects on the defined outcomes 43,44,46–51 . Verbal education was adopted in all effective educational programs.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among the included studies, 8 studies demonstrated positive effects on the defined outcomes 43,44,46–51 . Verbal education was adopted in all effective educational programs.…”
Section: Resultsmentioning
confidence: 99%
“…The frequency and duration of lectures varied among effective studies. Six studies 43,44,46–48,51 conducted 1 session, whereas 1 study 50 conducted 2 sessions. The mean duration of each lecture differed among studies, with a lecture duration of 15 minutes in 1 study, 51 30 minutes in 1 study, 48 45 minutes in 3 studies, 43,44,46 and 60 minutes in 2 studies 47,50 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations